2015
DOI: 10.1684/mst.2015.0454
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal prognosis for pulsating umbilical cord prolapse at the Befelatanana hospital of Madagascar

Abstract: L a procidence du cordon ombilical réalise un accident obstétrical grave de la période du travail, et constitue une cause importante de mortalité périnatale sans grever le pronostic de la mère. Définie comme la chute d'une anse du cordon ombilical au-devant de la présentation au moment de la rupture des membranes ou après celle-ci, elle expose le cordon à la compression, à la dessiccation ou à la mort réflexe, menaçant ainsi le pronostic foetal [1]. Il s'agit d'une extrême urgence d'extraction foetale. À Madag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
2
1
Order By: Relevance
“…This percentage is identical to what found at the same Hospital by Rakotozanany and al in 2010 finding a respective rate of 0.27% and Traoré in Mali in 2006 (0.27%). 1,4 In developed countries, our result is slightly higher than discovered by Gannard P and al (0.18%) in France, the United States of America (0.2%) and Singapore (0.12%). [5][6][7] But in reality the frequency of the cord prolapse varies according to factors.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…This percentage is identical to what found at the same Hospital by Rakotozanany and al in 2010 finding a respective rate of 0.27% and Traoré in Mali in 2006 (0.27%). 1,4 In developed countries, our result is slightly higher than discovered by Gannard P and al (0.18%) in France, the United States of America (0.2%) and Singapore (0.12%). [5][6][7] But in reality the frequency of the cord prolapse varies according to factors.…”
Section: Discussioncontrasting
confidence: 53%
“…These results are matching with those of the BUHCOG study in 2010 conducted by Rakotozanany and al, who found an average age of 28 years old, Gannard P and al (30 years old) with a predominance of the same age group. 4,5 In the literature, there is no direct influence of age in the occurrence of cord prolapse; it could be indirectly interfere with risk factors. Present study found that 51.43% of women were multiparous and 24.29% were primiparous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation